(untitled) (Baghdad Science Journal, 2025)
Adenosine deaminase (ADA; Ec: 3.5.4.4), 5´- Nucleotidase (5´– NT; Ec: 3.1.3.5), and AMP – amino hydrolase (AMP – deaminase AMPDA; Ec: 3.5.4.6) activities were measured in sera of ovarian cancer patients before surgery, and after chemotherapy. The results indicated that ADA specific activity increased significantly (P